Autophagy regulates neuronal excitability by controlling cAMP/protein kinase A signaling at the synapse. (11th October 2022) - Overhoff, Melina; Tellkamp, Frederik; Hess, Simon; Tolve, Marianna; Tutas, Janine; Faerfers, Marcel; Ickert, Lotte; Mohammadi, Milad; De Bruyckere, Elodie; Kallergi, Emmanouela; Delle Vedove, Andrea; Nikoletopoulou, Vassiliki; et al.
Abstract: Autophagy provides nutrients during starvation and eliminates detrimental cellular components. However, accumulating evidence indicates that autophagy is not merely a housekeeping process. Here, by combining mouse models of neuron‐specific ATG5 deficiency in either excitatory or inhibitory neurons with quantitative proteomics, high‐content microscopy, and live‐imaging approaches, we show that autophagy protein ATG5 functions in neurons to regulate cAMP‐dependent protein kinase A (PKA)‐mediated phosphorylation of a synapse‐confined proteome. This function of ATG5 is independent of bulk turnover of synaptic proteins and requires the targeting of PKA inhibitory R1 subunits to autophagosomes. Neuronal loss of ATG5 causes synaptic accumulation of PKA‐R1, which sequesters the PKA catalytic subunit and diminishes cAMP/PKA‐dependent phosphorylation of postsynaptic cytoskeletal proteins that mediate AMPAR trafficking. Furthermore, ATG5 deletion in glutamatergic neurons augments AMPAR‐dependent excitatory neurotransmission and causes the appearance of spontaneous recurrent seizures in mice. Our findings identify a novel role of autophagy in regulating PKA signaling at glutamatergic synapses and suggest the PKA as a target for restoration of synaptic function in neurodegenerative conditions with autophagy dysfunction. Synopsis: Accumulating evidence indicates that neuronal autophagy is not merely a housekeeping process. A new signaling role of autophagy in regulating PKA‐mediated phosphorylation of postsynaptic density protein further supports its adaptation to the unique requirement of neurons. Autophagy loss through neuron‐specific ATG5 deletion causes synaptic accumulation of 1α/β‐type regulatory (R) PKA subunits. Increased levels of R1α/β sequester the PKA catalytic subunit, resulting in decreased cAMP/PKA‐dependent phosphorylation of postsynaptic cytoskeletal proteins that mediate AMPAR trafficking. Mice with ATG5 deletion in glutamatergic neurons are characterized by augmented AMPAR‐dependent excitatory neurotransmission and exhibit spontaneous recurrent seizures. Abstract : Neuron‐specific deletion of ATG5 reveals an unexpected regulatory role of autophagy in signaling, further supporting that neuronal autophagy is adapted to the unique requirements of these cells.